Produksi Biomassa, Kadar N dan Bintil Akar Berbagai Leguminous cover crop (LCC) Pada Tanah Dystrudepts - Gian Sapta Adrialin; Wawan '; Yunel Venita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research was aimed to know biomass production, nitrogen fixation and root nodules by LCC on Dystrudepts. The research was conducted at the greenhouse of Faculty of Agriculture University of Riau from December 2013 to Maret 2014.This research was an experimental with 5 treatments (Mucuna pruriens, Pueraria javanica, Calopogonium mucunoides, Centrosema pubescens and Mucuna bracteata) with 4 replications and each replications consist of 4 plants. Data obtained from this study were analyzed by ANOVA and continued with Duncan’s New Multiple Range Test at 5%. The results showed that LCC panted on Dystrudepts produce different biomass, nitrogen fixation and also root nodules on Dystrudepts and Mucuna pruriens is better than Calopogonium mucunoides, Pueraria javanica, Centrosema pubescens and Mucuna bracteata. Key words: LCC, Dystrudepts, Mucuna pruriens.